2021
DOI: 10.3390/insects13010035
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Carabid Beetles in Grasslands of Northwestern China: Further Evidence of Insect Biodiversity Loss

Abstract: Ground-dwelling beetles are important functional components in nutrient-poor grasslands of middle temperate steppe ecosystems in China. Here, we assessed the changes in ground beetle (Coleoptera: Carabidae) communities in the grasslands of northwestern China over 12 years to improve the management and conservation of beetles all over the world. The Generalized Additive Model (GAM) was applied to estimate the changes in carabid beetle communities in two regions: a desert steppe (Yanchi region), and a typical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Changes in climatic conditions, including aridization, and related secondary causes, such as fires, droughts, and floods, influence the loss of diversity [11][12][13]. Toxic chemical pollution, urbanization, deforestation, and the introduction of invasive species have recently significantly impacted regional biodiversity [14][15][16][17][18]. Although Coleoptera have been studied better than many other invertebrate groups, their regional fauna in central European Russia has not yet been fully identified.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in climatic conditions, including aridization, and related secondary causes, such as fires, droughts, and floods, influence the loss of diversity [11][12][13]. Toxic chemical pollution, urbanization, deforestation, and the introduction of invasive species have recently significantly impacted regional biodiversity [14][15][16][17][18]. Although Coleoptera have been studied better than many other invertebrate groups, their regional fauna in central European Russia has not yet been fully identified.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons leading to recent changes in ecosystems. Urbanization, pollution with various toxic chemicals, regular fires, deforestation, climate changes, and biological invasions have recently had a considerable impact on biodiversity [11,[27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The response of groundwater table to rainfall runoff recharge has a hysteresis due to the impact of the groundwater flow field (Hocking and Kelly 2016), and the lag time is about 3-4 months. Liu (2021) showed that with the increase in the groundwater depth, the lag duration time of infiltration recharge is more obvious. When the groundwater depth reaches 8 m, the lag time of the peak value of irrigation infiltration recharge may reach more than 2-3 months.…”
Section: Discussionmentioning
confidence: 99%